The Effectiveness of Using the Zondaag Maandag Traditional Sports Game Model to Improve Learning Outcomes of Basic Motion for Children aged 10-12 Years - Abdul Hakim Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to see the effectiveness of using the traditional zondaag mandaag sports game model in improving the basic motion learning outcomes of children aged 10-12 years. The research method used to test the effectiveness with a quantitative descriptive approach using the True Experimental Design research design in the form of a Pretest-Postest Control Group Design. The research sample used was 60 students who were divided into 30 students of experimental class and 30 students of control class with a closed questionnaire instrument using a Likert scale of movement skills test adopted from the Test of Gross Motor Development. The results showed that the test data obtained Equal variances assumed and t-test for Equality of Means with a value of t = 17.877, df = 58 (n-2) and sig (2 tailed) or p-value = 0.000 <0.05 or H0 was rejected. Thus the hypothesis proposed is tested by the data so that it can be concluded that the results of learning the basic motion of the experimental group using the traditional zondaag mandaag sports game model are higher or more effective than the control group using conventional learning models.